The Empowering Farmers: Leveraging Digital Platforms to Enhance Sales at Koperasi Petani Jaya Makmur: Koperasi Petani Jaya Makmur - amir amir; Achmad Fauzan (Universitas Muhammadiyah Purwokerto, 2025)
Koperasi Petani Jaya Makmur is a cooperative that produces various processed food products such as vegetables, fruits, and various spices. Established in 2020, one of its flagship products is a new variety of papaya. However, to date, the cooperative has not had an official promotional website, which has limited the dissemination of information and sales to the broader public. One effort to enhance marketing to the public is by building a website as a digital marketing medium containing product information, activities, news, and more. The website creation process begins with collecting as much data as possible for content, followed by building the website and hosting it on a server using the official business domain. A website administrator is responsible for managing the website and its content. The website is expected to increase the cooperative's visibility among the general public in Indonesia and serve as the primary source of information for the cooperative.